Reading-Related Activities in English Textbook and The Way Teacher Exploited in the Classroom - Desyantaningsih, Ni Made Anggreoni; Artini, Luh Putu (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Students in junior high school level still face difficulties in understanding the text provided in textbook. The main cause is the textbook content that has not met the standards and the activities implemented by the teacher in the class are not optimal. The aims of this study were to analyse reading-related activities available in the English textbook used for Grade 8th junior high school and describe how the texts are exploited in the classroom by the teacher. The subjects of this study was English textbook used in the learning process and the English teacher. This research was conducted by applying qualitative descriptive analysis. Document analysis, classroom observation, and interviews were used to collect the data. The data is analyzed through four data analysis processes which involve data collection, data reduction, data display, and conclusion. The finding shows that there are reading-related activities found in English textbooks. The activities available in the English textbook are skimming/scanning, lexical items, inferring, questioning, and summarizing. Moreover, the text exploitation done by the English teacher in the classroom are short answer activity, multiple-choice tests, true/false activity, brainstorming activity, and completing activity.